Characteristics and risk assessment of agricultural meteorological disasters based on 30 years’ disaster data from Heilongjiang Province of China - Zhenxiang, Xing; Zhaorui, Yang; Qiang, Fu; Heng, Li; Xinglong, Gong; Jingyan, Wu (International Journal of Agricultural and Biological Engineering, 2017)
To determine the influence of agricultural meteorological disasters on agriculture in Heilongjiang Province, the disaster areas associated with different types of disasters and their variation characteristics were analyzed based on the statistical data of agricultural disasters from 1983 to 2013 in Heilongjiang Province, China. The moving average and the Mann-Kendall test were applied to identify the variation trends of drought, flooding, hailstorms and freezing (based on the disaster ratio and the disaster intensity index). Then, the Morlet wavelet analysis method was used to identify the periodicity of these four kinds of agricultural meteorological disasters. Finally, a fuzzy comprehensive evaluation method was adopted to analyze the degrees of agricultural loss induced by these disasters. The following results were obtained: 1) The disaster ratio and disaster intensity index for drought exhibited increasing trends; the disaster ratio and disaster intensity index for flooding exhibited decreasing trends; for hailstorms, the disaster ratio exhibited no obvious trend of change, whereas the disaster intensity index exhibited an increasing trend; and for freezing, the disaster ratio also exhibited no obvious trend of change, whereas the disaster intensity index exhibited a decreasing trend. 2) Mutation points were observed in the disaster ratio series for drought, flooding and hailstorms, whereas no mutation point was evident in the disaster ratio series for freezing. 3) Multiple time-scale characteristics were observed in the disaster ratio series for all four types of agricultural meteorological disasters. Furthermore, the disaster ratio series for the different types of disasters had different main periodicities. 4) From the perspective of the degree of agricultural loss induced by each type of disaster, drought was identified as the most severe type of agricultural meteorological disaster, followed by flooding, freezing, and hailstorms. The degree of agricultural loss caused by each type of disaster was different during different periods. Finally, based on the results, several strategies were identified for mitigating the effect of agricultural meteorological disasters in Heilongjiang Province.Keywords: agricultural meteorological disaster, disaster risk assessment, disaster ratio, disaster intensity index, fuzzy comprehensive evaluation, agricultural lossDOI: 10.25165/j.ijabe.20171006.2537Citation: Xing Z X, Yang Z R, Fu Q, Li H, Gong X L, Wu J Y. Characteristics and risk assessment of agricultural meteorological disasters based on 30 years’ disaster data from Heilongjiang Province of China. Int J Agric & Biol Eng, 2017; 10(6): 144–154.